A Privacy Model for RFID Tag Ownership Transfer. (5th March 2017) - Yang, Xingchun; Xu, Chunxiang; Li, Chaorong
Abstract : The ownership of RFID tag is often transferred from one owner to another in its life cycle. To address the privacy problem caused by tag ownership transfer, we propose a tag privacy model which captures the adversary's abilities to get secret information inside readers, to corrupt tags, to authenticate tags, and to observe tag ownership transfer processes. This model gives formal definitions for tag forward privacy and backward privacy and can be used to measure the privacy property of tag ownership transfer scheme. We also present a tag ownership transfer scheme, which is privacy-preserving under the proposed model and satisfies the other common security requirements, in addition to achieving better performance.